Pengembangan Sarana dan Prasarana untuk Mendukung Pariwisata Pantai yang Berkelanjutan (Studi Kasus: Kawasan Pesisir Pantai Wonokerto Kabupaten Pekalongan) - Fajriah, Syarifah Dina; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Tourism development is development that create added value in all aspects of tourism, ranging from infrastructure, attraction of Tourism, and other aspects. One of the tourism development, among others, the development of coastal tourism. The development must be carried sustainable coastal tourism development. Issues contained in the Wonokerto Coastal Area Tourism is not accommodated well as the existence of its good infrastructure and the absence of supporting public facilities that can support the activities of visitors and tourism are less well-organized system of coastal tourism management by government Pekalongan regency. Based on this, the need for sustainable development of coastal areas. To support this requires facilities that support to achieve all the Â requirements in order to optimize the area of tourism.